Healthcare Expenditures Associated with Persistent Opioid use Among Adults with Chronic Non-Cancer Pain Conditions: A Retrospective Cohort Study. (2nd July 2020) - Patel, Jayeshkumar; Shah, Drishti; Sambamoorthi, Usha
Abstract: Persistent opioid use in adults with chronic non-cancer pain (CNCP) conditions may lead to high economic burden due to adverse events associated with opioids. The objective of our study was to estimate the healthcare expenditures associated with persistent opioid use among adults with CNCP from both payer and patient perspectives. A retrospective cohort study using data from the Medical Expenditure Panel Survey (2012–2015) was undertaken. Patients with persistent, intermittent, and no opioid use in the baseline year were identified and their healthcare expenditures in the follow-up year were examined after controlling for potential confounders. In all, 7, 286 adults with CNCP matching our inclusion criteria were identified: 14%, 16%, and 70% reported persistent, intermittent, and no opioid use, respectively. Persistent and intermittent opioid use were associated with additional $4, 412 ($12, 468 vs $8, 056; P  < .001) and $1, 607 ($9, 663 vs $8, 056; P  = .004), respectively, in total healthcare expenditures compared to no opioid use. Moreover, persistent opioid use was associated with high out-of-pocket burden compared to no opioid use (adjusted odds ratio, 1.44; 95% confidence interval, 1.09–1.89). Our study shows that both payers and patients bear the brunt of economic burden of persistent opioid use. Alternative cost-effective strategies for pain management for this group of patients are needed.